Restructuring of an Ir(210) electrode surface by potential cycling - Soliman, Khaled A.; Kolb, Dieter M.; Kibler, Ludwig A.; Jacob, Timo (Beilstein Journal of Nanotechnology, 2014)
This study addresses the electrochemical surface faceting and restructuring of Ir(210) single crystal electrodes. Cyclic voltammetry measurements and in situ scanning tunnelling microscopy are used to probe structural changes and variations in the electrochemical behaviour after potential cycling of Ir(210) in 0.1 M H2SO4. Faceted structures are obtained electrochemically as a function of time by cycling at a scanrate of 1 V·s−1 between −0.28 and 0.70 V vs SCE, i.e., between the onset of hydrogen evolution and the surface oxidation regime. The electrochemical behaviour in sulfuric acid solution is compared with that of thermally faceted Ir(210), which shows a sharp characteristic voltammetric peak for (311) facets. Structures similar to thermally-induced faceted Ir(210) are obtained electrochemically, which typically correspond to polyoriented facets at nano-pyramids. These structures grow anisotropically in a preferred direction and reach a height of about 5 nm after 4 h of cycling. The structural changes are reflected in variations of the electrocatalytic activity towards carbon monoxide adlayer oxidation.
Keywords: CO adlayer oxidation; cyclic voltammetry; Ir(210) single crystal; potential cycling; scanning tunnelling microscopy; surface restructuring